Disarming the Ultimate Historical Challenge to Scientific Realism. (28th June 2018) - Vickers, Peter
Abstract: Probably the most dramatic historical challenge to scientific realism concerns Arnold Sommerfeld's ([1916 ]) derivation of the fine structure energy levels of hydrogen. Not only were his predictions good, he derived exactly the same formula that would later drop out of Dirac's 1928 treatment (something not possible using 1925 Schrödinger–Heisenberg quantum mechanics). And yet the most central elements of Sommerfeld's theory were not even approximately true: his derivation leans heavily on a classical approach to elliptical orbits, including the necessary adjustments to these orbits demanded by relativity. Even physicists call Sommerfeld's success a 'miracle', which rather makes a joke of the so-called 'no miracles argument'. However, this can all be turned around. Here I argue that the realist has a story to tell vis-à-vis the discontinuities between the old and the new theory, leading to a realist defence based on sufficient continuity of relevant structure. 1 Introduction 2 No Realist Commitment Required? 3 Enter the Physicists 4 A New Approach to the Non-relativistic Success 5 Relativity and Spin 6 Structure and Realist Commitment 7 Conclusion